Research Update: Density functional theory investigation of the interactions of silver nanoclusters with guanine - Dale, B. B.; Senanayake, R. D.; Aikens, Christine M. (My University, 2017)
Bare and guanine-complexed silver clusters Agnz (n = 2-6; z = 0-2) are examined using density functional theory to elucidate the geometries and binding motifs that are present experimentally. Whereas the neutral systems remain planar in this size range, a 2D-3D transition occurs at Ag5+ for the cationic system and at Ag42+ for the dicationic system. Neutral silver clusters can bind with nitrogen 3 or with the pi system of the base. However, positively charged clusters interact with nitrogen 7 and the neighboring carbonyl group. Thus, the cationic silver-DNA clusters present experimentally may preferentially interact at these sites. © 2017 Author(s).
Citation: Dale, B. B., Senanayake, R. D., & Aikens, C. M. (2017). Research Update: Density functional theory investigation of the interactions of silver nanoclusters with guanine. APL Materials, 5(5). doi:10.1063/1.4977795
Keywords: Bins; Nitrogen; Positive Ions; Binding Motif; Carbonyl Groups; Cationic Silver